Resolving an Inverse Cauchy Problem of Mixed Boundary Value of Bi-harmonic using a meshless collocation method - Leqaa Qasim Mohammed; Fatima M. Aboud (Academic Science Journal, 2024)
In this paper, a meshless collocation method using a polynomial expansion is proposed to solve a mixed fourth order differential boundary value problem. By employing the CGLS and PCG algorithms to solve some examples with different exact solutions, and by introducing noise for the input boundary data, the numerical stability of the suggested approaches is demonstrated.